2014
DOI: 10.12659/msm.890152
|View full text |Cite
|
Sign up to set email alerts
|

Platelet/lymphocyte ratio and risk of in-hospital mortality in patients with ST-elevated myocardial infarction

Abstract: BackgroundPlatelet-to-lymphocyte ratio (PLR) is a new prognostic marker in coronary artery disease. We aimed to evaluate the relationship between PLR and in-hospital mortality in patients with ST-elevated acute myocardial infarction (AMI).Material/MethodsThe present study included 636 patients with ST-elevated AMI. The study population was divided into tertiles based on their admission PLR. Patients having values in the third tertile was defined as the high PLR group (n=212) and those having values in the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…Because NLR and CRP can be easily obtained from routine laboratory examination in patients visiting the hospital due to acute chest pain, prediction of the prognosis in AMI patients with these biomarkers might be much easier and more comfortable than other biomarkers. PLR is also known as a good prognostic marker for cardiovascular events 21)22). In a previous study, combined NLR and PLR levels also predicted severity of CAD23) and adverse clinical outcomes 24).…”
Section: Discussionmentioning
confidence: 95%
“…Because NLR and CRP can be easily obtained from routine laboratory examination in patients visiting the hospital due to acute chest pain, prediction of the prognosis in AMI patients with these biomarkers might be much easier and more comfortable than other biomarkers. PLR is also known as a good prognostic marker for cardiovascular events 21)22). In a previous study, combined NLR and PLR levels also predicted severity of CAD23) and adverse clinical outcomes 24).…”
Section: Discussionmentioning
confidence: 95%
“…After that this marker was found to be associated with inflammation in cardiovascular diseases and positively correlated with SYNTAX score, GRACE risk and no-reflow phenomenon in ACS9202829. Most recently a series of studies have investigated the predictive importance of PLR in the adverse outcomes among ACS and reported inconsistent results9102229. We conducted this meta-analysis to comprehensively understand the prognostic role of PLR in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Temiz et al . reported that PLR was an independent predictor of in-hospital cardiovascular mortality in patients with ST-elevated acute myocardial infarction9. Ugur et al .…”
mentioning
confidence: 99%
“…Recently, PLR was found to be a new predictor of some cardiovascular diseases (25, 26). Thus, we evaluated PLR in our present study.…”
Section: Discussionmentioning
confidence: 99%